Implementation of MDLC method in development of game based animation for elementary school science subject - Putra, Eka; Dahroni, Andi; Prayitno, Budi; Palupiningsih, Pritasari (AIP conference proceedings, 2023)
The needs of the world of education that follow the development of technology make many parties able to follow these developments. It is not a taboo anymore that technology becomes a benchmark for the advancement of an educational institution. There are still many educators who do not keep up with technological developments so that the results of education are not optimal. E-Learning becomes the latest innovation to cover these disadvantages, the design of multimedia-based e-learning is considered to be one way to be able to learn and implement the technology. Supported by using the multimedia development life cycle method will make this research more systematic and structured, where this method has 6 stages, namely concept, design, material collecting, assembly, testing, and distribution. In this study, the research team collected data from science subjects in the first grade of elementary school. So later the teacher will not only teach conventionally as usual but can also apply the use of multimedia technology as support and learning attraction for each student. So that later graduates or students from each educational institution will become literate about technological developments as a whole. The purpose of this research is to develop games that can help the learning process of science for first-grade elementary school.